2022-VA-907-ESGO Laparoscopic laterally extended endopelvic resection and excision of isolated celiac trunk lymph node in recurrent low-risk endometrial cancer. (20th October 2022) - Giovannopoulou, Eirini; Kogeorgos, Stylianos; Saliaris, Konstantinos; Pandraklakis, Anastasios; Pistofidis, George; Lathouras, Konstantinos
Abstract : Introduction/Background: Background: Early stage (FIGO I) endometrial cancer is associated with a 10% risk of lymph node involvement. However, staging lymphadenectomy is reserved only for high-risk patients according to ESGO/ESTRO/ESP guidelines. Methodology: The study design is a narrated video presentation. We describe a case of a 54-year-old patient with a recurrence of low-risk endometrial cancer (endometrioid, Stage 1A, Grade 1) to the right external iliac lymph nodes and to an isolated celiac trunk lymph node 18 months after initial treatment that was treated by laparoscopy. Results: The patient was subjected to laparoscopic lateral extended endopelvic resection (LEER) for recurrent low-risk endometrial cancer that was fixed to the right lateral pelvic side wall. The recurrence in a lymph node at the celiac trunk was, also, excised. A macroscopically tumor free excision was achieved. No intraoperative complications occurred. Conclusions: Laparoscopic LEER is feasible, safe, and efficient to achieve complete excision of tumors that are fixed at the lateral pelvic side-wall for selected groups of patients. Safe performance requires deep knowledge of pelvic anatomy and a high level of experience. Further large high- quality studies are needed to estimate the long-term oncologic outcome of this approach.